THE DEVELOPMENT OF THE RIGHT TO MATERNITY LEAVE IN THE REPUBLIC OF CROATIA - LOOKING BACK AT THE PAST AND A LOOK INTO THE FUTURE (EU and comparative law issues and challenges series (ECLIC), 2024)
Today, the right to maternity leave is the right of an employed or self-employed pregnant woman, that is, an employed or self-employed mother, which she uses during pregnancy, childbirth and child care, and which has its own time and financial component. Since the accession of the Republic of Croatia to the European Union, Croatian legislation has been marked by the implementation of relevant European directives that emphasize gender equality and the balance of the private and business life of parents. However, if we look into the past, the situation was different. The aim of this article is to show the development of the right to maternity leave through different periods of Croatian legal history and, finally, by comparing the results with contemporary reality, question their continuity and suggest possible improvements. The article provides an overview of the time and financial components of maternity leave, the conditions for its realization, as well as the possibility of transferring it to the father. Applying the method of historical comparison of legal acts related to the topic of maternity leave, the article presents the development of legal acts, their current status in Croatian and contemporary European Union law, and proposes a perspective proposal for the future.